Jayaprakash Narayan - Edited by Anant Pai (Mumbai; Amar Chitra Katha, 2022)
Bandits and bullies both relied on his sense of fair play. When, as a boy, he tended to pet animals rather than play with his toys, people thought he was simple-headed. It was this spirit of kindness, however, that guided his lifelong fight against injustice and inequality. The rough and tumble of political life may have bewildered him but the country recognized in Jayaprakash Narayan an honest, brilliant and selfless Gandhian.
Keywords: Visionaries; Biography- Jayaprakash Narayan (1902-1979)